A study of an academic quality assurance system for an institute of technical education : from a total quality management perspective - Tan, Teck Hwa. (2008)
The purpose of the study is to examine the possibility of introducing an academic quality assurance system at ITE Dover, a technical institute of the Institute of Technical Education (ITE), Singapore, from a total quality management (TQM) perspective. Specifically, it aims to find out whether a TQM-based academic quality assurance system could succeed at ITE Dover, the positive steps to be taken and obstacles to be overcome when introducing TQM.